Structural characterization of the Longyearbyen CO2 Lab reservoir-caprock succession - Ogata K.; Senger K.; Braathen A.; Olaussen S.; Tveranger J. (Proceedings, Fourth EAGE CO2 Geological Storage Workshop, 2014)
This baseline study on fracture populations affecting the Mesozoic sedimentary succession of central Spitsbergen (Svalbard) has been performed to characterize the reservoir-caprock system explored for potential subsurface CO2 storage by the Longyearbyen CO2 Lab project. Integrating structural and stratigraphie analyses of outcrop and borehole data, we identified recurrent litho-structural and structural units (LSUs and SUs, respectively) on the basis of their fracture associations, lithologies and dominant sedimentary facies. A principal fracture settrending approximately E-W (J1) and a subordinate fracture set trending approximately N-S (J2) have been recognized. Subordinate systems of shear fractures (SI) trending roughly NE-SW and NW-SE, and a secondary low-angle, fracture set (S2) striking E-W to NW-SE have been observed. Their origin is interpreted as related to the far-field stress of the Paleogene West Spitsbergen fold-and-thrust Belt. The identified units are thought to influence the local hydrogeologic regime due to the intrinsic variations in the matrix and fracture network properties. The architecture of the reservoir-caprock succession is segmented, with the vertical alternation of intervals characterized by 1) fracture porosity and permeability, 2) microfracturing- related matrix porosity, and 3) preferential subsurface fluid flow pathways. Copyright © (2014) by the European Association of Geoscientists & Engineers. All rights reserved.